Role of moderate financial literacy as the influence of lifestyle on consumption behavior in senior high school students - Try Citra Puspitasari Lubis; Sutirman Sutirman (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to determine how moderation of financial literacy affects lifestyle on consumptive behavior in high school students in the Special Region of Yogyakarta. This research was conducted with a quantitative technical approach through causal associative research. Collecting data using a questionnaire questionnaire distributed in 3 high schools in the city of Yogyakarta. The research subjects were high school students consisting of 115 respondents. The results of the study show that there are problems with students' shopping behavior that leads to a consumptive lifestyle and financial literacy variables as a moderator in this study. with simple linear regression data analysis method and Moderated Regression Analysis (MRA) test. The results of the partial calculation show that the T-count has a number that is greater than the T-table with a T-count of 5.935 and a T-table of 1.981 with a tig sig of 0.000 <0.05 and a regression coefficient of 0.357, which means that lifestyle has a significant influence on consumptive behavior of class XI students of SMA Yogyakarta. The results of calculations using multiple linear regression analysis obtained that tcount is greater than ttable 5,640>1,960 with a sig value. 0.004 <0.05 so that it can be said that the financial literacy variable strengthens the lifestyle variable on the consumptive behavior of the eleventh grade students of SMA Yogyakarta.